HEMATOLOGICAL PROFILE OF THREE SPECIES OF Hipposideros spp. (HIPPOSIDERIDAE) AS AN ADAPTATION IN CAVE HABITAT, IN GUNUNG SEWU GEOPARK AREA, INDONESIA - Tatag Bagus Putra Prakarsa; Suwarno Hadisusanto; Satyawan Pudyatmoko; Ibnu Maryanto (Journal of Animal and Plant Sciences, 2023)
Bats that feed on insects and are members of the Hipposideridae family, category Chiroptera is widely dispersedworldwide, including Hipposideros spp. There are 29 species of 73 species that inhabit Indonesia. Most of these species use caves as their roosting habitat. In cave habitats, with different physicochemical conditions from surface habitats, the hematological profile can be a physiological indicator in responding to habitat conditions. This study aims to analyze the hematological profile of Hipposideros spp. as a parameter of physiological adaptation in the cave habitat in Gunung Sewu Karst Area, Indonesia. Sampling was carried out purposively in six caves locality of the Gunung Sewu karst area. Bats were collected with misnet (12 x 3 m), and Harpnet was installed at the entrance of the cave at 17.00 - 21.00 WIB.The Blood samples from each bat were taken intravenously, as much as 1 mL, on the Forearm and inserted into a 1.5 mL microtube that had been given EDTA anticoagulant. A total of 20 parameters were observed from erythrocyte, leukocyte, and platelet profiles. These parameters use a Hematology Analyzer for analysis. Data differences in hematological profiles between species and sex were analyzed using one-way ANOVA (sig= 95%), respectively. The relationship trend between the physicochemical parameters of the roosting area in the cave with erythrocytes and hemoglobin was then analyzed using a univariate linear model with multiple regression. All statistical analyses were performed using the Paleontological statistics program (PAST) ver. 4.09 and R. Studio v1.4.1717-3. We found three species (Hipposideros diadema, H. larvatus, and H. ater) with 70 individuals. This study concluded that there were differences in the hematological profiles between the three Hipposideros species based on species and gender, although some samples did not show significant differences based on statistical tests. Erythrocytes and hemoglobin can be used as parameters of physiological adaptation to cave habitats. This is indicated by an increase in erythrocytes and hemoglobin followed by a decrease in air temperature and oxygen levels, as well as increased humidity and ammonia levels in cave habitats. These study results can be supported if similar studies analyze the hematological profile of non-cave-roosting bat. It is recommended that future studies analyze the hematological profile of non-cave-roosting bats around the caves of the studies or in areas with similar conditions.
Keywords: Bat cave; hematology; Hipposideros; Microchiroptera; physiological adaptations